Biobanking in dentistry: A review. (November 2022) - Sivolella, Stefano; Scanu, Anna; Xie, Zijing; Vianello, Sara; Stellini, Edoardo
Abstract: Biobanks are not-for-profit services for the collection, processing, storage and distribution of biological samples and data for research and diagnostic purposes. In dentistry, biological materials and data obtained from questionnaires investigating oral conditions can be stored and used for large-scale studies on oral and systemic diseases. To give some examples: gene expression microarrays obtained on biobanked specimens were used in the identification of genetic alterations in oral cancer; efforts to identify genetic mechanisms behind dental caries have been based on an integrative analysis of transcriptome-wide associations and messenger RNA expression. One of the largest studies on facial pain was conducted using Biobank data. Cryopreservation of dental pulp stem cells is a common practice in tooth biobanks. With the exception of teeth and pulp, also leftover oral soft and hard tissues may represent a source of healthy samples that has rarely been exploited as yet. While biobanks are increasingly attracting the attention of the scientific community and becoming economically sustainable, a systematic approach to this resource in dentistry seems to be lacking. This review illustrates the applications of biobanking in dentistry, describing biobanked pathological and healthy samples and data, and discussing future developments.